Pengaruh Harga , Kualitas Produk dan Keragaman Produk Terhadap Keputusan Pembelian Dalam Membeli Produk CV Amanah Sentosa Tegal ( studi kasus pada toko brebes utara) - Yuni Inda Yani; Syariefful Ikhwan; Hendri Sucipto (STIKes Ibnu Sina Ajibarang, 2023)
Amanah Sentosa Tegal is a small company engaged in the distribution sector which provides snack food products. The aim of this research is to determine the influence of price, product quality and product diversity on purchasing decisions for CV Amanah Sentosa Tegal. The approach used in this research is an associative approach. The research population is infinite with a purposive sampling technique, so that a sample of 500 shops is taken. Data analysis techniques in this research use instrumental tests including validity and reliability, classical assumption tests including normality, multicollinearity, heteroscedasticity, multiple linear regression analysis, t test, F test, and determination test. data processing using the software program SPSS (statistical package for the social scienceb) 0.25 for windows. This is evidenced by the tcount value of 0.2646 > ttable of 0.1991 with a significance value of 0.040 <0.05. Partially, product quality variables influence purchasing decisions at CV Amanah Sentosa Tegal. This is evidenced by the tcount value of 2.086 < ttable of 0.1991 with a significance value of 0.035 > 0.05. And product diversity variables affect purchasing decisions at CV Amanah Sentosa Tegal. This is evidenced by the tcount value of 2.975 < ttable of 0.1991 with a significance value of 0.004 > 0.05. and the price variable is the most dominant variable y. This is evidenced by the Fcount value of 39.450 > Ftable of 2.49.